CO-MORBID DEPRESSION AND ALCOHOL USE DISORDER AMONG YOUTH LIVING WITH HIV ATTENDING A COMPREHENSIVE CARE CLINIC AT A PRIVATE HOSPITAL IN NAIROBI, KENYA - ABANJA WILLIAM OTIENO. (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2020)
BACKGROUND: Psychiatric morbidity has been associated with HIV disease since the beginning of the AIDS epidemic. In youth with HIV infections alcohol use and depression make the management more difficult and worsen the prognosis. Alcohol use also have adverse interactions with the medications used hence reducing the effectiveness of the medications. Globally, depression is one of the leading causes of illness and disability among adolescents. Dispite this, minimal research has been done locally on the prevalence of various psychiatric morbidities associated with HIV infection with none focusing on youth aged 15-24years old. STUDY OBJECTIVE: To determine the prevalence of depression and alcohol use disorder among youth aged 15-24yrs under care for HIV & AIDS. DESIGN: Cross sectional analytical study design. STUDY SITE: Comprehensive Care Clinic (CCC) of Mater Misericordiae Hospital, Nairobi Kenya. METHOD: Survey method of HIV infected youth aged 15-24 yrs under CCC was used. Participants were given researcher designed questionnaire and subjected to both Alcohol Usue Disorder Inventory Test (AUDIT) and Beck’s Depression Inventory (BDI) which are selfadministered tests to a total of 194 participants. Analysis and presentation of results were done using statistical models and SPSS software. RESULTS: The prevalence of alcohol use disorder was 13% and the prevalence of depression was 77%. The sociodemographic factors that did not influence either or both alcohol use disorder and depression with a P-value above .05 were level of education, religion, residence and marital status. Income, occupation, gender and age had a strong association with both alcohol use disorder and depression at a P value of .000. The study also established an association between alcohol use disorder and depression at an Odd ration of 0.04. CONCLUSION: Youth with HIV/AIDS aged 15-24yrs receiving treatment still experience considerable alcohol use disorder and depression. These youths can benefit from improved delivery of psychiatric care adjunct to psychotherapy during follow up in CCC. RECOMMENDATION: In order to solve the twin problem of alcohol use and depression among HIV infected youth, key stakeholders need to design multidimensional strategies to educate youth while creating impetus for them to avoid alcohol use and receive comprehensive screening, diagnosis and treatment of depressive symptoms. It would be vital for preventive strategies to be implemented in all CCC’s programes